The protection of personal data - Nicola Boccella; Riccardo Misuraca; Pierpaolo Tudisco Thor (International Journal of Technology for Business (IJTB), 2020)
With the exponential growth of digitization and electronic market, personal data has taken on a key role for all individuals actively involved in the process. Any type of transaction, from the payment of a product or service to registration on a web site, requires extensive use of information and personal data. In this paper we will analyse the process of collection and transmitting personal data from a practical and regulatory point of view. In particular, after describing the nature and principles governing their dissemination, the paper analyses the main stages that European regulation has taken over time. The aim is to analyse the behaviour that companies and consumers must adopt in order to ensure compliance with current legislation. In addition, the paper deals with the different systems of attacking personal data by hackers and the respective countermeasures that can be taken by companies to protect their customers.
Keywords: 650; Personal Data; Privacy; General Data Protection Regulation; European Union; Cyber Crime